Crystal growth of Dirac semimetal ZrSiS with high magnetoresistance and mobility - Sankar, Raman (Sci Rep, 2017)
High quality single crystal ZrSiS as a theoretically predicted Dirac semimetal has been grown successfully using a vapor phase transport method. The single crystals of tetragonal structure are easy to cleave into perfect square-shaped pieces due to the van der Waals bonding between the sulfur atoms of the quintuple layers. Physical property measurement results including resistivity, Hall coefficient (R(H)), and specific heat are reported. The transport and thermodynamic properties suggest a Fermi liquid behavior with two Fermi pockets at low temperatures. At T = 3 K and magnetic field of Hǁc up to 9 Tesla, large magneto-resistance up to 8500% and 7200% for Iǁ((100)) and Iǁ((110)) were found. Shubnikov de Haas (SdH) oscillations were identified from the resistivity data, revealing the existence of two Fermi pockets at the Fermi level via the fast Fourier transform (FFT) analysis. The Hall coefficient (R(H)) showed hole-dominated carriers with a high mobility of 3.05 × 10(4) cm(2) V(−1) s(−1) at 3 K. ZrSiS has been confirmed to be a Dirac semimetal by the Dirac cone mapping near the X-point via angle resolved photoemission spectroscopy (ARPES) with a Dirac nodal line near the Fermi level identified using scanning tunneling spectroscopy (STS).